AN EXPERIMENTAL MODEL OF ALCOHOL INDUCED HEPATIC INJURY AT FEMALE RATS - Kovalyov, G.A.; Petrenko, A.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the work of original model of alcohol induced hepatic injury at female rats including three stages issubmitted: the first stage is selection of animals inclined to alcoholization; the second stage is accustoming ofanimals to alcohol; the third stage is intensive alcoholization, at this stage the consumed doze of alcohol made14-18 g/kg of weight of a body in days. Use of the given model on female rats results in almost triple increaseof activity ALT and AST in plasma of blood, more than to triple increase of duration hexane sleep, more thanto double increase prothrombin time, almost triple decrease of the contents albumin in plasma of blood, that istypical of alcohol induced hepatic injury. The offered model does not contradict to the principles of bioethicsas excludes the violent introduction of alcohol accompanied with stress.